2012
DOI: 10.1002/mrd.22079
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of unrestricted somatic stem cells as a feeder layer to support undifferentiated embryonic stem cells

Abstract: The use of unrestricted somatic stem cells (USSCs) holds great promise for future clinical applications. Conventionally, mouse embryonic fibroblasts (MEFs) or other animal-based feeder layers are used to support embryonic stem cell (ESC) growth; the use of such feeder cells increases the risk of retroviral and other pathogenic infection in clinical trials. Implementation of a human-based feeder layer, such as hUSSCs that are isolated from human sources, lowers such risks. Isolated cord blood USSCs derived from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 19 publications
0
26
0
Order By: Relevance
“…Moreover, human umbilical cord blood (CB)-derived USSCs have previously been proved to have a vast differentiation potential and regenerative benevolent effects when applied in animal models of multiple degenerative diseases. It has also been suggested that CBderived USSCs could significantly contribute in wound healing and be potentially used in cell therapy in some genetic skin diseases including recessive dystrophic epidermolysisbullosa (10,11).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, human umbilical cord blood (CB)-derived USSCs have previously been proved to have a vast differentiation potential and regenerative benevolent effects when applied in animal models of multiple degenerative diseases. It has also been suggested that CBderived USSCs could significantly contribute in wound healing and be potentially used in cell therapy in some genetic skin diseases including recessive dystrophic epidermolysisbullosa (10,11).…”
Section: Discussionmentioning
confidence: 99%
“…Somatic stem cells are distinct but capable to differentiate into mesenchymal cells (bone cells, chondrocytes), endodermal cells, neural cells, but not into endothelial stem or progenitor cells and hematopoietic lineage stem or progenitor cells and adipocytes characterized in that the USSC expresses the DLKl -gene the Arvand J Health Med Sci 2016;1(1):17-26 expression being preferably detectable and measurable using RT-PCR assay and/or on the protein level and that it is a clonally selected and expanded cell (10,16,17). Unrestricted adherent pluripotent isolated cells from umbilical cord blood (USSCs) have the capability to differentiate into osteoblasts, blood cells, chondrocytes, neurons, hepatocytes, and heart tissue under ex vivo conditions (10,17). USSCs express different factors, including growth factors, adhesion molecules and various cytokines such as SCF, TGF1b, IL-6, G-CSF, VEGF, GM-CSF, M-CSF, LIF, Flt3 ligand, TPO, SDF-1a, IL-15, IL-12, HGF, IL-8, and IL1b (10).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations